If you're not out selling, you're being outsold - Lawrence, Michael St. (John Wiley & Sons, 1998)
"If You're Not Out Selling, You're Being Outsold is more than a 'how-to-sell' book. St. Lawrence and Johnson have approached the art of selling from a witty, entertaining, and inspirational view. The authors candidly recognize what ingredients are required for reaching success, and they have blueprinted a constructive approach that can apply to anyone, whether they are contemplating entering sales, or have made sales their career."-Nicholas D. Wolkonsky Director of Sales, High Volume Division, Western Region, ADT Security Services, Inc."If You're Not Out Selling, You're Being Outsold is an inspiring book written by two professionals who actually do sell. I found the principles and techniques easy to follow and implement. I am buying copies of this book for all my sales managers."-Robert Coakley Divisional Director of Sales, Alamo Rent A Car, Inc.No matter what sort of business professional you are, you have to sell to succeed: make yourself heard, make your ideas known, convince others to act on them. No matter what you're selling, you need confidence, energy, and, above all, a positive attitude. If You're Not Out Selling, You're Being Outsold shows you how to energize your outlook, sell your ideas, produce top-quality work, and make others want to do business with you.